Te Utu - Collier, Zayne (Te Kaharoa, 2020)
Whangape, 1528, ko Korekore te whiwhia te maramataka. Taiao and his army went hunting for birds and set snares. While they were there, Taiao saw the gutless pig, who killed his father twelve years ago. After Taiao saw Te Pō in the distance, he instructed his troops with his taiaha to stop and be stealthy. Taiao crouched under the cover of the bushes and watched, stalking Te Pō and his small ope. While watching Te Pō, Taiao had intermittent, yet vivid flashbacks of the night his papa kāinga was attacked by Te Pō and his troops, 12 years ago.